Mental health in China: exploring the impacts of built environment, work environment, and subjective perception - Fang, Zhou; Lin, Yu; Chen, Chuangyuan; Jiang, Jian; Dong, Letian (Frontiers in Psychology, 2024)
The shifting living and working conditions have profound impacts on the residents' mental health. However, current research in this field has not remarkable investigated. Therefore, this study used the China Labor-force Dynamic Survey (CLDS) dataset from 2018 and relied on a regression model to examine the effects of the built environment, work environment, and subjective perception on the mental health of Chinese citizens. It also considers the circumstances of both migrants and local residents. The results of this study revealed significant correlations between mental health and greening space rate, road network density, commuting time, work feelings, community trust, economic satisfaction and other factors. Additionally, the mental health of local residents was shown to be significantly affected by community security, while its shows no significant in migrants. Furthermore, a significant spatial autocorrelation was found in terms of mental health within the central and eastern regions of China. The findings of this study offer valuable insights that can be used to facilitate measures aimed at improving the mental health of residents and promoting the development of healthy cities.